HIV-1 Uncoating and Nuclear Import Precede the Completion of Reverse Transcription in Cell Lines and in Primary Macrophages - Francis, Ashwanth C. (Viruses, 2020)
An assembly of capsid proteins (CA) form the mature viral core enclosing the HIV-1 ribonucleoprotein complex. Discrepant findings have been reported regarding the cellular sites and the extent of core disassembly (uncoating) in infected cells. Here, we combined single-virus imaging and time-of-drug-addition assays to elucidate the kinetic relationship between uncoating, reverse transcription, and nuclear import of HIV-1 complexes in cell lines and monocyte-derived macrophages (MDMs). By using cyclophilin A-DsRed (CDR) as a marker for CA, we show that, in contrast to TZM-bl cells, early cytoplasmic uncoating (loss of CDR) is limited in MDMs and is correlated with the efficiency of reverse transcription. However, we find that reverse transcription is dispensable for HIV-1 nuclear import, which progressed through an uncoating step at the nuclear pore. Comparison of the kinetics of nuclear import and the virus escape from inhibitors targeting distinct steps of infection, as well as direct quantification of viral DNA synthesis, revealed that reverse transcription is completed after nuclear import of HIV-1 complexes. Collectively, these results suggest that reverse transcription is dispensable for the uncoating step at the nuclear pore and that vDNA synthesis is completed in the nucleus of unrelated target cells.